2018
DOI: 10.1519/jsc.0000000000001857
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mild Hypohydration on Muscle Endurance, Power, and Strength in Healthy, Active Older Men

Abstract: Goulet, EDB, Mélançon, MO, Lafrenière, D, Paquin, J, Maltais, M, and Morais, JA. Impact of mild hypohydration on muscle endurance, power, and strength in healthy, active older men. J Strength Cond Res 32(12): 3414-3424, 2018-Under particular circumstances older persons may be vulnerable to developing mild chronic hypohydration. In young adults, hypohydration has been shown to impair muscle endurance, power and strength. Muscle performance declines with aging, a condition known as dynapenia. How hypohydration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…In our opinion, among these factors, myocite hydration could play a relevant role. Our results also agree with those published by Goulet et al, who suggest that acute dehydration of 1% of body weight in healthy active 60 to 75 years old mencould affect muscle endurance, power and strength [25]. Moreover, the correlation between ICW and muscle strength has also been observed in young adult athletes [26], with some authors suggesting that cell volume is a metabolic signal that regulates cellular function and also that cellular swelling leads to anabolism and cellular shrinkage promotes catabolism and protein degradation [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…In our opinion, among these factors, myocite hydration could play a relevant role. Our results also agree with those published by Goulet et al, who suggest that acute dehydration of 1% of body weight in healthy active 60 to 75 years old mencould affect muscle endurance, power and strength [25]. Moreover, the correlation between ICW and muscle strength has also been observed in young adult athletes [26], with some authors suggesting that cell volume is a metabolic signal that regulates cellular function and also that cellular swelling leads to anabolism and cellular shrinkage promotes catabolism and protein degradation [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we identified worsening balance in elderly people, and these results are in line with those published in literature. [4952] However, we also recorded altered balance in young age, probably due to a lack of muscle strength (dynapenia) that is present at this age. [53] Authors reported children's lack of key motor skills (strength, power, coordination) that are necessary components for the balance capacity [5356] ; this provides us with a possible explanation of altered balance at early age.…”
Section: Discussionmentioning
confidence: 93%
“…Muscular strength is determined by many factors and, in the elderly, it seems to be more related to the quality of the muscle and its ability to contract and generate strength than to the quantity of muscle. Few studies have evaluated the effect of intracellular hydration on muscle function in the elderly, but some authors have suggested that muscle intracellular hydration could be an indicator of muscle quality and contractile capacity [105,106,107,108]. Ritz reported an increase in ECW with ageing, especially among people with disabilities or altered health conditions [106].…”
Section: Cell Hydration Functional Capacity and Frailtymentioning
confidence: 99%